2020
DOI: 10.1039/c9sc04336e
|View full text |Cite
|
Sign up to set email alerts
|

Target identification among known drugs by deep learning from heterogeneous networks

Abstract: Target identification and drug repurposing could benefit from network-based, rational deep learning prediction, and explore the relationship between drugs and targets in the heterogeneous drug–gene–disease network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 249 publications
(183 citation statements)
references
References 120 publications
2
181
0
Order By: Relevance
“…After adding its target, an RNA helicase enzyme EIF4A 76 , silvestrol was predicted to be significantly associated with HCoVs (Z = -1.24, P = 0.041) by network proximity analysis. To increase coverage of drug-target networks, we may use computational approaches to systematically predict the drug-target interactions further 25,26 . In addition, the collected virus-host interactions are far from completeness and the quality can be influenced by multiple factors, including different experimental assays and human cell line models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adding its target, an RNA helicase enzyme EIF4A 76 , silvestrol was predicted to be significantly associated with HCoVs (Z = -1.24, P = 0.041) by network proximity analysis. To increase coverage of drug-target networks, we may use computational approaches to systematically predict the drug-target interactions further 25,26 . In addition, the collected virus-host interactions are far from completeness and the quality can be influenced by multiple factors, including different experimental assays and human cell line models.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology allows to identify several candidate repurposable drugs for Ebola virus 11,14 . Our work over the last decade has demonstrated how network strategies can, for example, be used to identify effective repurposable drugs 13,[22][23][24][25][26][27] and drug combinations 28 for multiple human diseases. For example, network-based drug-disease proximity sheds light on the relationship between drugs (e.g., drug targets) and disease modules (molecular determinants in disease pathobiology modules within the PPIs), and can serve as a useful tool for efficient screening of potentially new indications for approved drugs, as well as drug combinations, as demonstrated in our recent studies 13,23,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, without foreknowledge of the complete drug-target network, development of promising and affordable approaches for effective treatment of complex diseases is challenging. 10 Because drug targets do not operate in isolation from the complex system of proteins that comprise the molecular machinery of the cells with which they associate, each drug-target interaction (panel) should be examined in an integrative context (figure 2). 11 Therapeutic interventions need to consider the perturbation of disease system properties (termed network medicine [panel]), and have little to do, functionally speaking, with genetic and genomic events alone.…”
Section: Emerging Challenges and Opportunities In Drug Discoverymentioning
confidence: 99%
“…In vitro experimental evidence also validated the predicted targets of this known drug [9]. Further, combined with in silico prediction, in vitro validation and animal phenotype model demonstrated that, topotecan, a topoisomerase inhibitor also had the potential to act as a direct inhibitor of human retinoic-acidreceptor-related orphan receptor-gamma t (ROR-γt) [10].…”
Section: Introductionmentioning
confidence: 75%